2013
DOI: 10.5194/bgd-10-13277-2013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biogeochemical characterization of the riverine organic matter transferred to the NW Mediterranean Sea

Abstract: A large amount of terrestrial organic matter is annually delivered by rivers to the continental shelf, where this material is either buried or transferred to the deep sea by hydrodynamic processes such as storms. The relative amount of terrestrial organic matter in the marine sediments is often determined by analyzing the stable isotopes (δ13C and δ15N) and the C / N ratio of organic matter because the various particulate organic matter (POM) sources have distinct isotopic c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 71 publications
1
2
0
Order By: Relevance
“…This preferential sediment transport path along the slope would prevent this flux of particles to reach intermediate water column depths at the central part of the GoV (station Ct) and even deeper parts of the GoV basin (station Cb). Similar events of storm-related sediment resuspension and its subsequent along-current transport have also been observed in the Gulf of Lions (Bourrin et al, 2008;Higueras et al, 2014), even with wave heights of 2.5 m (Palanques et al, 2012). The time decoupling between meteorological events and the magnitude of the TMF in each of the traps suggest that TMF peaks in the GoV can develop by a sequential combination of Ebro River discharges and sporadic storm events.…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 57%
“…This preferential sediment transport path along the slope would prevent this flux of particles to reach intermediate water column depths at the central part of the GoV (station Ct) and even deeper parts of the GoV basin (station Cb). Similar events of storm-related sediment resuspension and its subsequent along-current transport have also been observed in the Gulf of Lions (Bourrin et al, 2008;Higueras et al, 2014), even with wave heights of 2.5 m (Palanques et al, 2012). The time decoupling between meteorological events and the magnitude of the TMF in each of the traps suggest that TMF peaks in the GoV can develop by a sequential combination of Ebro River discharges and sporadic storm events.…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 57%
“…The d 13 C value, explaining significant amounts of variability in the microbial communities, is also an indicator of the source of the organic carbon. The d 13 C values in our samples ranged from À 27.67 to À 25.83, indicating a predominant contribution of the Rhô ne River particulate OM (POM) (Darnaude et al, 2004;Higueras et al, 2014) at the expense of the marine contribution (Harmelin-Vivien et al, 2008). Higueras et al (2014) demonstrated that depleted d 13 C values (o À 27%) characterized freshwater production in several Mediterranean rivers whereas enriched d 13 C values (4 À 27%) traced predominantly the soil OM.…”
Section: Discussionmentioning
confidence: 97%
“…*Some samples are missing because they contained o450 sequences. a m À 3 s À 1 ; b mg g À 1 dry weight (DW) sediment; c mg g À 1 DW sediment; d terrestrial fraction was calculated using the d 13 C value and a two end-members model, where terrestrial end-member was d 13 C ¼ À 27.4 ± 0.7% and marine end member is d 13 C ¼ À 20.1 ± 0.8% (Harmelin-Vivien et al, 2008;Higueras et al, 2014); e median particle diameter (mm); f the coloring is different only if the values were significantly different (Po0.05); g samples where the variance was too large to determine whether differences/similarities were significant.…”
Section: Resultsmentioning
confidence: 99%